Em defesa das causas sagradas da igreja católica: Padre Luiz Gonzaga do Monte e o projeto de neocristandade (Brasil, primeira metade do Século XX) - Lopes, Bruna Rafaela de Lima (Universidade do Vale do Rio dos Sinos, 2021)
In this thesis, we analyze the strategies used to achieve the goals of Neo-Christianity, based on the intellectual trajectory of Canon Luiz Gonzaga do Monte (1905-1944) - built and grounded on the principles of this movement -, seeking to discuss how and why it was described as holy and wise by biographers and lay and religious admirers. We start from the hypothesis that the wisdom and holiness imputed to Monte can be explained from four elements, whose reach can only be understood if considered together, namely: the guidelines adopted by the Catholic Church in the first half of the 20th century; the action of intellectuals from Natal and admirers of Monte; the trajectory of Monte itself, as well as the networks of social relationships he established, and the political culture experienced in Natal during his period of priesthood and after his death. We defend, therefore, that the image of saint and wise built on Padre Monte were strategically used both to comply with the guidelines established by the Catholic Church at the time, as they emanated and were consecrated due to the personal and institutional networks in which he participated. To support the investigation, newspapers were used, in particular, A Ordem, books written by Monte and three biographies produced about him, in addition to the ten volumes of the Antologias do Padre Monte and interviews. The thesis, which uses the theoretical-methodological framework of Cultural History, Political History and Intellectual History, in productive dialogue with Italian micro-history, is structured in three chapters, in which family life and priestly formation are addressed; his acting as a teacher and clergyman and the networks of personal relationships he built and the spaces for sociability he frequented. It discusses strategies adopted by Monte's admirers to present him as a "man superior to other men", a man "beyond his time", based on the identification of when and under what circumstances this image of Monte was built, who built it and what representations were mobilized for this construction, taking into account both what Monte's admirers said about him until his death in 1944 and after his death. It also discusses how he expressed his views on internationally debated issues that affected the Catholic Church, such as liberalism, Communism, Nazism, Freemasonry, the Rotary Club, as well as in relation to issues related to science, such as Biology, Medicine and Spiritism. The polemics that Monte waged, based on Catholic Apologetics, with its supposed adversaries, considered enemies of the Catholic Church, also deserved attention. From the analysis of his manifestations in the press, we demonstrate that the cleric was an active agent of Neo-Christianity in Brazil, contributing significantly to the Church regaining its power and prestige. If, on the one hand, the networks of relationships that Monte formed, intellectual productions and polemics with opponents of the Church contributed to achieving this goal, on the other, after his death, his admirers continued this project, reinforcing their wisdom and holiness.
Keywords: Luiz Gonzaga do Monte; Neocristandade; Polêmicas; Ciência e espiritualidade; Santidade e sabedoria; Neo-christianity; Polemics; Science and spirituality; Holiness and wisdom; ACCNPQ::Ciências Humanas::História